Gestation and Reception of Alfonso D. Castelao’s 'Os vellos non deben de namorarse' - Tato Fontaíña, Laura (Madrygal. Revista de Estudios Gallegos, 2019)
The article examines the long process of gestation of the play, Os vellos non deben de namorarse, by Alfonso Castelao, and its subsequent reception by audiences in Buenos Aires. Based on the evidence of letters, press notes, newspaper articles, play manuscripts and reviews of the play’s eventual opening, three phases of writing and development have been identified: Art Theatre (1921-1923), Masked Theatre (1934-1936), and the play itself (1939-1941). Particularly close attention has been paid to the two differing play manuscripts, now preserved at the Museum of Pontevedra. The rest of the paper analyses the reception of the play from two different perspectives: that of traditional audiences for Galician plays in the Argentine capital, and that of more discerning, specialist spectators, both local and emigrant. The conclusion argues that the ‘Epilogue’ was a late addition to the play, included by Castelao at the last minute in an attempt to popularise the text to fit his audience’s tastes; its success motivated him to continue his writing for the theatre. The paper also features an annex section containing a previously uncollected article by Castelao, first published in the newspaper, Crítica, in 1941.
Keywords: Castelao; Galician Drama; Reception; Literary Criticism; History of Theatre